Revitalizing Hadhrami Authority: New Networks, Figures and Institutions among Ḥabā’ib in Indonesia - Syamsul Rijal (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2020)
This article analyses the rising popularity of young ḥabā’ib and their da‘wah activism in contemporary Indonesia. The popularity of ḥabā’ib has also been followed by the proliferation of media and publications promoting both Hadhrami scholars and Hadhramaut. Distinct from scholars who emphasise domestic considerations, this study sees transnational connection as crucial to the facilitation of the ḥabā’ib’s da‘wah activism. The article argues that the reestablishment of ties between Indonesia and Yemen in 1990 in the field of education and preaching (da‘wah) has facilitated the growing authority of ḥabā’ib in Indonesia. These new connections have enabled young Indonesian Muslims to travel to Hadhramaut to study in traditional Islamic seminaries and to build their own da‘wah networks. By examining these new connections, this article pays particular attention to the charismatic Hadhrami scholar, Habib ‘Umar ibn Hafiz, his role and influence, as well as his students’ network in contemporary Indonesia.